The Relationship of Cultural Dimension and Servant Leadership of Police Officer - I Gede Nyoman Bratasena; Tb. Ronny Rahman Nitibaskara; Vita Mayastinasari; Surya Dharma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to determine the relationship of the cultural dimension and Indonesian National Police (INP) officer servant- leadership. Culture variable used the theory of cultural dimensions by Geert Hofstede, consisting of high-power distance vs. low power distance; individualism vs. collectivism; masculinity vs. femininity; high uncertainty avoidance vs. low uncertainty avoidance; long term vs. short term orientation; and indulgence vs. restraint. INP officer leadership variable used the theory of servant-leadership, using the ten dimensions of servant hood, integrity, awareness, listening, healing, develop others, build teamwork, have vision, shared decision making, and persuasion. This research uses a quantitative approach to data collection methods survey techniques. The survey was conducted using a conventional questionnaire and an online questionnaire. The sampling technique is done using simple random sampling method. Research conducted on 633 respondents representing INP officers’ population numbered 42.446 people, who were working at the Police Headquarters and 32 regional police across Indonesia. Data analysis technique using a correlation test of Kendall's Tau. This research has found 39 significant relationships